Learn Java for Android development - Friesen, Jeff (Apress, 2010)
10 chapters: Getting Started with Java; Learning Language Fundamentals; Learning Object-Oriented Language Features; Mastering Advanced Language Features Part 1; Mastering Advanced Language Features Part 2; Exploring the Basic APIs Part 1; Exploring the Basic APIs Part 2; Discovering the Collections Framework; Discovering Additional Utility APIs; Performing I/O